American colonial education a case study of selected local Filipino educators. - Calibara, Ma. Christine A.
This research paper documents the life and experiences of the four local educators namely Adriano Cabardo, Esteban Amparo, Perpetua Amparo, and Elena Amparo. As this paper aims to show and document their lives, it also aims to connect their life experiences particularly to the educational system introduced by the American colonizers, which greatly affected the flow of their careers. The educational system made them one of the pioneer teachers in their respective hometown due to the training that they had. The teaching career was not only the product of the said educational system for them, but also, this system gave them opportunities to improve their skills on their field such as in music, and writing. The researcher concludes that the educational system as used by the Americans in colonizing Philippines, it also became a room for opportunities for other people to improve their way of life as exemplified by the life and experiences of these four (4) local educators.